Optical and Electrical Characteristics of CdO thin films deposited by Spray Pyrolysis Method (Journal of Bangladesh Academy of Sciences, 2009)
Cadmium oxide (CdO) thin films have been deposited by a locally developed spray pyrolysis method onto glass substrate at 473K. The optical and electrical properties of the as-deposited and annealed films are studied in details. The surface morphology of the samples was studied by scanning electron microscopy (SEM). The SEM micrograph of as-deposited film shows uniform deposition over the substrate well. The optical absorption coefficient (Î±) of the CdO films was determined from transmittance spectra in the range of wavelength 450 - 650nm. For different thicknesses (130nm ~ 380nm) of as-deposited films, the direct band gap is found in the range of 2.40 ~2.51 eV and indirect band gap in the range of 1.97 ~ 2.20 eV. Resistivity (Ï) of CdO thin film was measured in the temperature range of 303 to 553K. The resistivity of the films of different thickness initially increases with increase in temperature and reaches a maximum at 430K and then decreases with further increase of temperature. The resistivity of the film exhibits metallic behaviour up to 430 K and above that the film behaves like a semiconductor. Activation energy (ÎE) in the semiconductor region is found in the range from 0.049 to 0.075 eV for films of thickness ranging from 160 - 285 nm. Keywords: Spray pyrolysis, CdO, Resistivity, Optical band gap, Activation energy doi: 10.3329/jbas.v32i1.2447 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 97-105, 2008